Evaluation of Sensitization Program on Occupational Health Hazards for Nursing and Allied Health Care Workers in a Tertiary Health Care Setting - Naithani, Manisha; Khapre, Meenakshi; Kathrotia, Rajesh; Gupta, Puneet Kumar; Dhingra, Vandana Kumar; Rao, Shalinee (Frontiers in Public Health, 2021)
Background: Occupational health hazard pertaining to health care providers is one of the neglected areas that need serious attention. Any compromise in their safety would result in reduction in workforce, which may affect patient care, keeping in mind the wide gap between the required number and actual health care workers (HCWs) available in the world over. Aim: This study was undertaken to evaluate the change in knowledge through a sensitization training program on occupational health hazards and vaccination for HCWs. Materials and Methods: Participants of the study included nursing and allied HCWs of a tertiary care health institute in Uttarakhand, India. Multiple training sessions, each of around 180 min, were held periodically in small groups with 20–40 participants over 2 years. Participants were assessed with pretest and posttest questionnaires, and feedback was taken. Questionnaires comprised three categories: general safety and ergonomics, biological hazards, and chemical and radiation hazards. Data of incident reporting for needlestick injury from 2017 to 2019 were retrieved. All data were compiled in Excel sheet and analyzed. Results: A total of 352 participants were included in the study. Mean ± SD for pretest and posttest scores were 5.3 ± 2.13 and 11.22 ± 2.15, respectively. There was considerable improvement in knowledge, which was found to be statistically significant with p-value of 0.001 for all categories. Participants in their feedback suggested for inclusion of psychosocial aspect in further training programs. Conclusion: Low baseline knowledge prior to attending the course highlights a need for an intervention through such structured sensitization program to create awareness and educate HCWs on common occupational health hazards and vaccination. Statistically significant improvement in posttest knowledge highlights effectiveness of the training program. A drastic rise in incident reporting for needlestick injury reflects fairly good impact of training program. Regular and appropriate form of training can reduce injuries resulting from occupational hazards and ensure healthy workforce contributing toward a positive impact on national economy.